A State of Physical Development of Children from Gdańsk and Elbląg Voivodeships - Gacka, Ewa; Wojciechowska, Jolanta (Anthropological Review, 1981)
In order to evaluate physical development of children from the territory of Gdansk and Elblag voivodeships 826 girls and 965 boys aged 6-10 years were measured in large towns, small towns and villages. Data on body height, weight and Quetelet’s index were collected. Results show that children living in large towns have higher values of observed characters. However, with application of t test it has been. found that the majority of differences between body measurements of town and countryside children are statistically insignificant. This suggests gradual disappearance of differences resulting from living conditions.